Environmental Learning as a Unique Context for Science Education (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
Challenges faced by science and environmental educators in respect to the distinctions and interrelationships between these fields have been many over the past few decades. While some scholars note contradicting epistemologies and purposes in their critique of the nature of an environmental (science) education, this paper considers another perspective: through participatory methods it examines how environmental learning may form a unique and qualitatively different context for science education. The paper also highlights a collaborative inquiry into the practices of environmental learning as it is enacted in formal school curriculums in British Columbia, Canada. Our efforts involved critical document analysis of frameworks and resources from around the world. Focus groups and interviews conducted over a period of 16 months informed a collaborative writing process that included teachers, academics and government officials. The framework produced offers a conceptual view for environmental learning in all settings (including science) while providing several principles of teaching and learning to guide educators in designing activities for varied learning contexts. The framework provides a number of perspectives around which environmentally-focused lessons may be developed and demonstrates that environmental education should included scientific understandings but be broadened to include other forms of knowledge including aesthetic appreciation, social responsibility and the development of an environmental ethic.